Dissertation: MSc International Business BUSI4027 UNUK - Jiraphongchaikul, Chotirat (2020)
Multinational corporations have embarked on internalisation as a mean of achieving competitiveness and higher performance in the competitive market. Therefore, most of companies have realised the importance of foreign direct investment in expanding to new markets especially in countries. This research investigates outward internalisation and foreign direct investment (FDI) as well as motives of Caterpillar Inc. in moving into Asian market. The main importance of this research was to provide important information to Caterpillar Company and other multinational companies that would need moving into new markets. The main research objectives of the study was to find the attributes of Asian market as an investment destination as well as motives for Caterpillar’s international expansion to Asian market. The second objective was to investigate impacts of Asian market on Caterpillar’s expansion in Asian market and the third objective was to investigate the impacts of adopted foreign direct investment strategy on Caterpillar’s performance in South Korea, Malaysia, China and Philippines. The study used internalisation theory, Dunning’s OLI theory, Monopolistic advantage theory and Vernon’s theory to study country factors and motives of companies expanding into new countries. Previous studies have shown that researchers have contributed significant information in the field of foreign direct investment, its advantages, and reasons for foreign direct investment and factors that affect organisation’s foreign direct investments. The study was qualitative in nature and it used secondary information from Caterpillar annual reports, reports from other significant sources and country reports. The findings shows Asian market is characterised by presence of trade laws and regulations, restrictions, political instability and competition from local industries that affects the performance of foreign direct investments in the country. The findings also shows that foreign direct investments have positive impacts on Caterpillar Inc. performance since it increases company revenue through sales. The study recommends that a further study should be conducted on other markets except Asian market to understand effects that foreign direct investment in such countries would perform and issues that would affect Caterpillar Company in such areas.